Lynx lynx lynx (Linnaeus 1758 ... - Jo, Yeong-Seok; Baccus, John T.; Koprowski, John L. (Zenodo, 2018)
Lynx lynx (Linnaeus, 1758) —Eurasian Lynx Felis lynx Linnaeus, 1758 p.43; Type locality- Southern Sweden. Felis cervaria Temminck, 1827 p.106; Type locality- Northern Asia. Lynx lynx borealis: Kuroda in Uchida, 1927 p.37. L. borealis: Kishida & Mori, 1931 p.379. L. lynx cervaria: Won, 1958 p.442; Won, 1967 p.152. F. lynx cervaria: Kuroda, 1938 p.40; Won, 1968 p.320. F. lynx lynx: Yoon, 1992 p.113 L. lynx: Han, 1994 p.46; Won & Smith, 1999 p.20; Oh, 2004a p.154. Range: The distribution of the Eurasian lynx formerly covered the northwestern Korean Peninsula (Kim et al. 2015; Fig. 53). Only two lynx records from the 1910s at Guseong City, Pyeonganbuk Province and in the 1930s at Deokcheon City, Pyeongannam Province documented its presence in Korea (Won 1968). Recent records of lynx in North Korea are from Sinheung-gun and Baekam-gun in the 1990s (Kim et al. 2015). Unofficial records around the DMZ from South Korea cannot be validated (Yoo 2000). Historically, L. lynx has always been considered rare in ... : Published as part of Jo, Yeong-Seok, Baccus, John T. & Koprowski, John L., 2018, Mammals of Korea: a review of their taxonomy, distribution and conservation status, pp. 1-216 in Zootaxa 4522 (1) on pages 83-85, DOI: 10.11646/zootaxa.4522.1.1, http://zenodo.org/record/2610198 ...